Pyrimidino piperazinyl acetamides : innovative class of hybrid acetamide drugs as potent antimicrobial and antimycobacterial agents - Kanagarajan, V. (2013)
A series of new 2-(4-methylpiperazin-1-yl)-N-(4,6-diarylpyrimidin-2-yl)acetamides (34 – 42) have been synthesized and tested for their in vitro antimicrobial and antimycobacterial properties. Compounds 34, 39 against S. aureus, 39 against β-H. Streptococcus, 42 against V. cholerae, 40 – 42 against E. coli, 38, 39 against K. pneumonia, and 37 – 41 against P. aeruginosa showed excellent antibacterial activity by inhibiting the growth of the respective organisms at a minimum inhibitory concentration of 6.25 μg/mL. Noteworthy compounds 40 against A. flavus, 34 against M. indicus, 40, 42 against R. arrhizus and M. gypseum also exhibited excellent antifungal activity by inhibiting the growth of these microorganisms, at a minimum inhibitory concentration of 6.25 μg/mL. Moreover, compounds 36, 38, and 40 – 42 showed promising antitubercular activity by inhibiting the growth of M. tuberculosis H 37 Rv and clinically isolated isoniazid-resistant M. tuberculosis strains.